2021
DOI: 10.48550/arxiv.2109.00403
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing Gravitational Slip with Strongly Lensed Fast Radio Bursts

Tal Abadi,
Ely D. Kovetz

Abstract: The rapid accumulation of observed Fast Radio Bursts (FRBs) originating from cosmological distances makes it likely that some will be strongly lensed by intervening matter along the line of sight. Detection of lensed FRB repeaters, which account for a noteworthy fraction of the total population, will allow not only an accurate measurement of the lensing time delay, but also follow-up high-resolution observations to pinpoint the location of the lensed images. Recent works proposed to use such strongly-lensed FR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…Finally, we showed that for low masses (M 30 M ), increasing sensitivity contributes more to the f DM bound than increasing the number of FRBs. We suggested to do so by stacking repeating FRBs (a focus of several recent strong lensing analyses [31][32][33][34]) and demonstrated the potential to improve the constraints on PBH dark matter.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we showed that for low masses (M 30 M ), increasing sensitivity contributes more to the f DM bound than increasing the number of FRBs. We suggested to do so by stacking repeating FRBs (a focus of several recent strong lensing analyses [31][32][33][34]) and demonstrated the potential to improve the constraints on PBH dark matter.…”
Section: Discussionmentioning
confidence: 99%